Magnitude and influencing factors of parasomnia in schoolchildren - Choudhury Habibur Rasul; Khan Golam Mostafa; Nitya Nanda Baruri; Jakia Sultana (Paediatrica Indonesiana, 2013)
Background Parasomnias are undesirable events occurring inthe sleep-wake transition period. Several predisposing factors arereported to induce parasomnia in preschool children.Objective To es timate the magnitude of parasomnia in schoolchildren and to evaluate its relationship with possible predisposingfactors .Methods Five hundred children aged 5- 16 years from a boys'school and a girls' school in Khulna City, Ban gladesh, wererandomly selected for the study conducted fromJuly to December2011. The survey was don e in two steps: self-administeredquestionnaire and clinical interviews of affected students andtheir parents. Apart from demographic features, questionnairesincluded details of perinatal and personal fac tors as well asfamilial and socioeconomic factors . The diagnoses of variantsof parasomnias was based on the criteria for category-basedclassification by the American Academy of Sleep Medicine.Results Seven hundred thir teen filled questionnaires revealedparasomnia in 187 (26.2%) children. Most parasomnias wereaccompanied by other sleep disorders, in which 23 (12.3%) havingprimary dyssomnias including 18 (9.3%) obstructive sleep apnea,and 10 (5.3%) parasomnias with hypersomnias . Nightmares(7. 4%) were highest among the parasomnias fo llowed by nocturnalenuresis (4.1 %) and sleep terrors (3 .4%). More girls experiencedparasomnias than boys (107 /360 vs . 80/353, respectively;P= 0.039) . Perinatal factors such as problems during pregnancy(17 .1 %) or eventful delivery (25. 7%), and socioeconomic factorssuch as familial disharmony (11.8%) and low socioeconomiclevel(3 1.6%) had positive associations with parasomnia.Conclusion One-quarter of school children experience parasomnia.We found perinatal factors particularly problem duringpregnancy, and socioeconomic factors particularly familialdisharmony have significant influences on this condition.